Elucidating the mechanism of soybean-derived protein hydrolysate in stabilizing rice yield and enhancing agronomic efficiency - Zhang, Shunchang; Tang, Lijuan; Zhan, Xing; Wang, Dianwen; Zhang, Anning; Wu, Hao; Huang, Cheng; Chen, Hongping; Wang, Jilin (Frontiers in Plant Science, 2025)
IntroductionAs a type of biostimulant, protein hydrolysates (PHs) can promote crop growth, increase yield, and enhance crop tolerance to abiotic stresses. However, their application and research in rice production remain relatively limited.MethodsFocusing on“Lifenggu” (a soybean-derived protein hydrolysate), this study carried out multilocation field trials to evaluate the real-world application efficacy of this biostimulant on rice production across varying environmental conditions. Meanwhile, laboratory-based assays were conducted to analyze the doseresponse of rice growth to “Lifenggu” and its protective mechanisms under high-temperature and herbicide stress.ResultsField experimental results showed that “Lifenggu” could increase rice yield by 8.9%-14% (with an average increase of 10%). Physiological analysis revealed that “Lifenggu” might promote biomass accumulation by increasing the SPAD value of rice and enhancing the activity of nitrogen metabolic enzymes. Under herbicide and high-temperature stress, “Lifenggu” could alleviate the adverse effects caused by stress and reduce yield losses, possibly by increasing the activity of antioxidant enzymes and the content of proline, while decreasing the contents of malondialdehyde (MDA) and hydrogen peroxide (H2O2). Further transcriptomic analyses demonstrated that “Lifenggu” regulates the expression of genes involved in phytohormone biosynthesis, stress response pathways, and secondary metabolism.DiscussionThis, in turn, serves as the molecular mechanism enabling its dual functions of promoting rice growth and improving stress tolerance. These results deepen insights into the yield-increasing effects of protein hydrolysates in rice, and offer both theoretical support and practical recommendations for their application in rice cultivation.